Atherosclerosis and Thrombosis: Lessons from Animal Models - Badimon, Lina (Thrombosis and Haemostasis, 2001)
Atherothrombosis defines the occurrence of thrombosis on athero-sclerotic lesions. Atherosclerosis is the most prevalent disease of our time and its thrombotic complications are responsible for an exceedingly high number of deaths and disabilities. Over the past few years, experimental investigation and clinical and pathologic observations have led to a better understanding of how a thrombus forms and also of its incidence in acute ischemic syndromes. A thrombus is usually found secondary to atherosclerotic plaque disruption. Mural thrombosis, also at the site of plaque rupture, is an important mechanism in the progression of atherosclerosis even when symptoms are absent. Because atherosclerosis is a silent and asymptomatic disease until complications arise with thrombosis producing clinical symptoms, it is necessary to have models that reproduce the human disease in its early stages. Unfortunately, not all the experimental models of vascular disease have human resemblance and validity. Knowledge of the disease process and of what an experimental animal model can offer is a milestone for a successful investigation. Experimental models of vascular disease have enhanced our understanding of the pathophysiological processes leading to vascular obstruction in both spontaneous and accelerated atherosclerosis and thrombosis. Animal models have provided insight into the role of platelets, lipids, renin-angiotensin system (RAS), cytokines and growth factors in the evolution and progression of atherosclerosis and have suggested potential therapeutic interventions. Significant advances in our understanding of the vascular biology and pathology of atherosclerosis and thrombosis, and of the interactions of blood cells, lipids and proteins with the vascular wall, have allowed us to formulate new experimental hypotheses and to test therapeutic strategies, either pharmacological or surgical.
Keywords: Atherosclerosis; thrombosis; animal models; risk factors; platelets